Design and Development Of an Iot-Based Water Quality Monitoring System In The Palm Oil Industry At PT. PKIS - Nina Hairiyah; Alya Rahmaida; Risna Dwi Latifah; Imron Musthofa; Jihan Pradesi; Fina Pradika Putri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2025)
The availability of clean water is a vital element in the operational processes of palm oil mills, serving both processing and domestic needs. PT. PKIS operates a Water Treatment Plant (WTP) to treat raw water from reservoirs into clean water that meets quality standards. However, the existing manual monitoring system for water quality poses a risk of delays in detecting fluctuations in critical parameters such as pH and turbidity. This study aims to design and implement an Internet of Things (IoT)-based water quality monitoring system capable of real-time monitoring of pH and turbidity parameters. The system design was conducted over five months within the industrial environment of PT. PKIS, utilizing pH and turbidity sensors integrated with an ESP32 microcontroller and the Blynk application platform for data visualization. The testing results indicate that the pH sensor demonstrates a satisfactory accuracy level with a margin of error of 2,20%, while the turbidity sensor exhibits suboptimal performance with a margin of error of 1,30%. The implementation of this system is expected to enhance the effectiveness of water quality monitoring, expedite decision-making processes, and ensure that the treated water meets the established standards, thereby supporting the sustainability of palm oil industry operations.